2016
DOI: 10.15294/biosaintifika.v8i3.6448
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Polycyclic Aromatic Hydrocarbon Pyrene by Biosurfactant-Producing Bacteria Gordonia cholesterolivorans AMP 10

Abstract: Pyrene degradation and biosurfactant activity by a new strain identified as Gordonia cholesterolivorans AMP 10 were studied. The strain grew well and produced effective biosurfactants in the presence of glucose, sucrose, and crude oil. The biosurfactants production was detected by the decreased surface tension of the medium and emulsification activity. Analysis of microbial growth parameters showed that AMP10 grew best at 50 µg mL -1 pyrene concentration, leading to 96 % degradation of pyrene within 7 days. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…After 7 and 11 days of incubation, the tetramethrin was degraded by over 70% and 95%, respectively. It can be assumed that strain A16 can utilize tetramethrin as a sole source of carbon for growth, Previous researchers reported that the Gordonia species showed potential to degrade other organic pollutants [25][26][27]. However, Gordonella has not been reported to degrade pyrethroid pesticides, so there is still room for exploration and development of the biodegradation ability of pyrethroid pesticides by Gordonella.…”
Section: Growth Linked Degradation Of Tetramethrin With Strain A16mentioning
confidence: 99%
“…After 7 and 11 days of incubation, the tetramethrin was degraded by over 70% and 95%, respectively. It can be assumed that strain A16 can utilize tetramethrin as a sole source of carbon for growth, Previous researchers reported that the Gordonia species showed potential to degrade other organic pollutants [25][26][27]. However, Gordonella has not been reported to degrade pyrethroid pesticides, so there is still room for exploration and development of the biodegradation ability of pyrethroid pesticides by Gordonella.…”
Section: Growth Linked Degradation Of Tetramethrin With Strain A16mentioning
confidence: 99%
“…Kurniati et al [47] observed the ability to degrade pyrene in Gordonia cholesterolivorans strain AMP 10. The strain G. iterans Co17 utilized naphthalene and anthracene in oil with degradation rates of 55.3% and 63.2%, respectively.…”
Section: Introductionmentioning
confidence: 99%